Study on Distribution of Rhododendron Arboreum Sm. In Langtang National Park Using Geographic Information System and Remote Sensing - Shrestha, Ila (Tribhuvan University Journal, 2016)
The paper is based on the study of distribution of Rhododendron arboreum Sm. in Langtang National Park ranging from 600 m to 7234 m. The study was carried out the Remote-Sensing and Geographic Information System technique. SPOT Image and ERDAS Software have been used for the image processing. The program has detected different ecological parameters in tropical to alpine zone and verified ground truth Rhododendron arboretum of the study.